Modelling of material removal rate in electro discharge machining of nonconductive ZrO₂ Ceramic with kerosene and EDM oil dielectric fluid / Abdus Sabur … [et al.] - Sabur, Abdus (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2014)
In this study electro discharge machining (EDM), a noncontact material removing process, is used for structuring nonconductive Zr02 ceramic. Adhesive copper foil is applied on the workpiece surface as assisting electrode to initiate the sparks. Experiments are conducted according to Taguchi approach by varying the peak current (Ip), pulse-on time (Ton), pulse-off time (Toff) and gap voltage (Vg)for two different dielectric fluids kerosene and EDM oil. The optimized parametric conditions are determined for higher MRR by the analysis of variances (ANOVA) and signal to noise (S/N) ratio. The results showed that Ip is the most significant parameter of MRR for both the dielectric fluids. It is also shown that EDM of ZrO₂ with kerosene dielectric gives about 1.6 times more MRR compared to EDM oil. However, inferior surface finish is observed in SEM investigation when kerosene dielectric is used. Optimum values of Ip Ton, Toff and V are identified for EDM of ZrO₂ with kerosene dielectric.